Desain Antarmuka Android untuk Monitoring Energi Listrik Berbasis IoT - Pramathana, Raindra; Dharma, Agus (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 2 No 2 (2024): JNATIA Vol. 2, No. 2, Februari 2024DO - 10.24843/JNATIA.2024.v02.i02.p03, 2024)
This paper presented the design of an Android user interface for monitoring electricity usage based on the Internet of Things (IoT). Adoption of using IoT devices in the energy sector increase rapidly, there is a need for user-friendly interfaces that allow users to monitor and manage their electricity consumption effectively. The proposed research was designing of Android interface which provides real-time information on energy usage, allowing users to track their electricity consumption patterns, set energy-saving goals, and receive alerts or recommendations for optimizing energy usage. The design emphasizes a visually appealing and intuitive interface, enabling users to easily navigate through energy-related data and control connected devices remotely. The interface leverages IoT technology to collect and display data from smart power meters or connected devices, enhancing energy awareness, and promoting energy-efficient behaviors. The effectiveness of the interface is evaluated through user studies, considering factors such as usability, user satisfaction, and energy conservation behavior.